2023
DOI: 10.1002/uog.26183
|View full text |Cite
|
Sign up to set email alerts
|

Pre‐eclampsia screening in Denmark (PRESIDE): national validation study

Abstract: What are the novel findings of this work?This study is an independent validation of the Fetal Medicine Foundation (FMF) first-trimester screening algorithm for pre-eclampsia, completed in a predominantly white low-risk population in Denmark. We found that the FMF algorithm was effective in the Danish population and it had higher detection rates for preterm pre-eclampsia compared with the current Danish strategy based on single major maternal risk factors. What are the clinical implications of this work?This st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 50 publications
(77 reference statements)
3
17
0
3
Order By: Relevance
“…The finding of this study that the triple test is among the best-performing screening strategies for preterm PE is consistent with the results of previous studies 5,7,[20][21][22][23][24][25] . Likewise, it was shown previously that the predictive performance of the triple test for term PE was poor.…”
Section: Comparison With Findings Of Previous Studiessupporting
confidence: 93%
“…The finding of this study that the triple test is among the best-performing screening strategies for preterm PE is consistent with the results of previous studies 5,7,[20][21][22][23][24][25] . Likewise, it was shown previously that the predictive performance of the triple test for term PE was poor.…”
Section: Comparison With Findings Of Previous Studiessupporting
confidence: 93%
“…13 A double-blind, placebo-controlled trial of low-dose aspirin (81 mg daily) versus placebo from 6 to 13 weeks of gestation until 36 weeks in 11 976 nulliparous women with singleton pregnancies found that aspirin was associated with an 11% reduction in the risk of PTB at <37 weeks of gestation (RR 0.89, 95% CI 0.81-0.98) but the study did not provide data as to whether the PTB was spontaneous or iatrogenic and whether there was any association with pre-eclampsia. 26 In our study, we demonstrated the poor or no impact of aspirin in sPTB and iPTB in the absence of pre-eclampsia and the high impact on the prevention of iPTB associated with pre-eclampsia.…”
Section: Outcome Measurementioning
confidence: 50%
“…2,6,20 The model, which was originally described in 2012, was subsequently validated in many studies in the UK and other countries that reported high predictive performance for preterm pre-eclampsia and good agreement between estimated risk and observed incidence of the disease. [21][22][23][24][25][26][27] In the absence of serum PlGF, serum PAPP-A can be used, but the performance of the latter is poor by comparison with PlGF. 28 Additionally, the studies reported that in screening for pre-eclampsia it is a necessity to establish a programme for continuous quality assurance of biomarker measurements, as is the case in screening for fetal trisomies in the UK.…”
Section: Interpretation Of Results and Implications For Clinical Prac...mentioning
confidence: 99%
See 2 more Smart Citations